Ordenamiento Territorial Como Propuesta De Desarrollo Económico Local Estudio De Caso: Propuesta De Plan De Desarrollo Y De Ordenamiento Territorial Para El Cantón Alausí, Componente Económico Productivo - Bernal, Catalina Margarita Verdugo; Riera, Ángela Paulina Rivera; Sampedro, Otto Fernando Balseca; Nuñez, Edwin Fernando Viteri; Layedra, Jaime Robert Guevara; Moyota, Paulina Beatriz Díaz; Guerra, Juan Hugo Rodríguez (European Scientific Journal, ESJ, 2016)
An economic development and land use planning proposal for Alausí County, Chimborazo was created as part of this research. The research started with an analysis of the current situation in the productive area of the county. With the help of participative workshops, it was possible to identify principal problems and opportunities; these topics helped in the definition of development strategies. Alausí is a rural area with 76% employment. Most are engaged in farming activities on sandy loam soils with slopes ranging from 15 to 45 degrees. Despite the ruggedness, 39% of the area is appropriate for farming activities, in which the principal products are barley, corn, potato, and fresh milk. Access to technology is a principal barrier to economic growth and profitability in production. It is recommended that the municipality of Alausí implement various projects identified by this research in order to capitalize on the productive area of the county and to improve quality of life.